2010
DOI: 10.1007/s00442-010-1856-1
|View full text |Cite
|
Sign up to set email alerts
|

Fit females and fat polygynous males: seasonal body mass changes in the grey-headed flying fox

Abstract: When females and males differ in their timing of maximum reproductive effort, this can result in sex-specific seasonal cycles in body mass. Such cycles are undoubtedly under strong selection, particularly in bats, where they affect flying ability. Flying foxes (Old World fruit bats, Pteropus spp.) are the largest mammals that can sustain powered flight and therefore face critical trade-offs in managing body reserves for reproduction, yet little is known about body mass dynamics in this group. I investigated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 65 publications
(86 reference statements)
3
21
0
5
Order By: Relevance
“…These results agree with those reported in a histological study in a population of L. yerbabuenae of Chamela, Jalisco [34]. Also, in this study we found that the testicular mass varied seasonally similar to body mass, indicating a close relationship between spermatogenesis and the individual condition, as in P. poliocephalus [10].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results agree with those reported in a histological study in a population of L. yerbabuenae of Chamela, Jalisco [34]. Also, in this study we found that the testicular mass varied seasonally similar to body mass, indicating a close relationship between spermatogenesis and the individual condition, as in P. poliocephalus [10].…”
Section: Discussionsupporting
confidence: 93%
“…However, in L. yerbabuenae happens that while fat accumulates, it also increases the size of the testis and epididymis, as well as the quantity and quality of sperm stored in the epididymis, prior to the mating period that start in late May and through June [6]. This seasonal phenomenon of fat accumulation and testicular activity increase , in mammals, is not new, was described originally for primates [30], and is known as " fatted male phenomenon", has also been reported in Pteropus poliocephalus [10] as well as in large mammals like ungulates [31], pinnipeds [32] and ursids [33], among others. However, here is the first time that the ratio between fat and sperm parameters was studied.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An alternative explanation is that more productive males sacrificed time they might have spent away from their territory for some other reason, such as for foraging. Male Grey-headed Flying-foxes (Pteropus poliocephalus) appear to sacrifice foraging time in favour of remaining on a territory, losing up to 20% of their body mass during the breeding season through territory defence and lost foraging opportunities (Welbergen 2011). Male Black Grouse (Tetrao tetrix) also lose mass while defending breeding territories on leks: more successful males, typically those with higher lek attendance, lose more mass than do less successful males at the lek periphery (Rintamaki et al 2001;Lebigre et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The differing measures used to establish body condition demonstrated similar temporal trends. Fitness-maximising strategies of males and females typically differ, particularly with respect to timing of maximal reproductive effort, resulting in sex-specific seasonal cycles in body mass, body condition and fat deposition (Lindstedt and Boyce, 1985;Welbergen, 2011).…”
Section: Temporal Variationsmentioning
confidence: 99%